2022
DOI: 10.1128/aac.00676-22
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Clinical Risk Models for Clostridioides difficile-Attributable Outcomes

Abstract: Clostridioides difficile is the leading health care-associated pathogen, leading to substantial morbidity and mortality; however, there is no widely accepted model to predict C. difficile infection severity. Most currently available models perform poorly or were calibrated to predict outcomes that are not clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In the largest external validation to date, our group recently reported that these models yielded AUC scores below 0.70 [ 14 ]. A recent study in a similarly sized cohort in Virginia also showed poor performance of published models upon external validation [ 27 ]. Thus, current models cannot reliably predict risk for severe complications from CDI.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest external validation to date, our group recently reported that these models yielded AUC scores below 0.70 [ 14 ]. A recent study in a similarly sized cohort in Virginia also showed poor performance of published models upon external validation [ 27 ]. Thus, current models cannot reliably predict risk for severe complications from CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike predicting CDI severity, where a multitude of clinical severity scoring systems exist with reasonable performance, such as ATLAS ( 47 , 48 ), there are currently no well-established tools to predict the recurrence of C. difficile infection. We used a naive Bayesian approach to evaluate a rich set of novel predictors shown to be important in CDI pathogenesis ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…18 Further details regarding the retrospective cohort and how risk models were selected from the literature and calculated are previously-described. 4 …”
Section: Methodsmentioning
confidence: 99%
“… 3 Existing C. difficile outcome models are trained to predict only one or a composite of severe outcomes with varying degrees of clinical importance and no model simultaneously predicts severe outcomes and recurrence. For instance, the ATLAS score, perhaps the top-performing risk model, 4 was originally trained to predict “clinical failure” (lack of markedly improved diarrhea or need for additional C. difficile therapy based on investigator opinion 5 ) and is not useful for predicting future recurrent infection.…”
Section: Introductionmentioning
confidence: 99%